2011
DOI: 10.3109/s10165-010-0373-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of single-dose mizoribine for patients with rheumatoid arthritis: results at 6 months after switching from a multiple-dose regimen without a change in total daily dose

Abstract: To determine the efficacy and safety of single-dose mizoribine (MZR) for patients with rheumatoid arthritis (RA), a 6-month, single-arm, open-label, prospective observation study was performed. In patients who had been taking MZR at 100-150 mg/day in 2-3 divided portions continuously for at least 3 months, and who had shown a lack of clinical response, or escape (defined as a lack of response at the time of switching, even if some form of response had been shown before that), multiple-dose administration was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…MZR was approved by the Japanese Ministry of Health, Labour and Welfare in 1984. Since then, MZR has been widely used in Japan for renal transplantation and rheumatic diseases, including RA [10][11][12] and SLE. [13][14][15] Nomura et al 13 reported that 12 patients with SLE were successfully treated with glucocorticoid, MZR and tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MZR was approved by the Japanese Ministry of Health, Labour and Welfare in 1984. Since then, MZR has been widely used in Japan for renal transplantation and rheumatic diseases, including RA [10][11][12] and SLE. [13][14][15] Nomura et al 13 reported that 12 patients with SLE were successfully treated with glucocorticoid, MZR and tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
“…23 Compared to these agents, MZR's strong point is its safety. MZR can be safely used for elderly people, 11,12,15 and therefore, is a promising agent in the treatment of PMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation